Quality assured spatial dataset of wildfire containment firelines and engagement outcomes 2017 to 2024 - Arkowitz, Alexander; Ritter, Scott M.; Thompson, Matthew P.; Young, Jesse D.; Pietruszka, Brad; Calkin, David E. (Scientific data, 2025)
The escalation of wildfires in the USA, coupled with rising firefighting costs and decreasing workforce capacity, underscores the critical need to evaluate the efficiency and effectiveness of containment measures. However, the existing spatial data that records the locations and types of containment measures and wildfire perimeters contains numerous errors and redundancies. This paper presents a comprehensive fireline Quality Assurance and Quality Control dataset developed from the wildland firefighting operations data reported in the National Interagency Fire Center National Incident Feature Service. This improved dataset contains reliable spatial locations for fireline built during suppression operations, the associated verified fire perimeters, and identifies where containment was success or failure for fires greater than 1000 acres from 2017–2024. The improved final dataset represents critical information that was previously unavailable for assessing the success of fireline operations and incident management resource-use efficiency. The lessons learned from analyses utilizing this dataset are critical for improving the efficiency and effectiveness of the United States wildfire management system.